2013
DOI: 10.1097/phh.0b013e3182571708
|View full text |Cite
|
Sign up to set email alerts
|

Siglang Buhay

Abstract: Using culturally specific organizations to deliver NPA interventions was feasible and effective among Filipino-Americans. Similar multilevel approaches should be investigated in other cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 8 publications
(7 reference statements)
1
43
0
Order By: Relevance
“…Cultural adaptations and individual tailoring, or subgroup analysis of outcomes of interest was not reported for the Asian American subgroups in these three large RCT studies. Following these study exclusions, seven studies were identified for review (Sun et al, 1996, Liao et al, 2002, Han et al, 2010, Qi et al, 2011, Dirige et al, 2013, Islam et al, 2013, Wang et al, 2013). Table 1 provides a descriptive summary of reviewed studies including: RTC design characteristics, sample characteristics, intervention characteristics, cultural appropriateness assessment, risk of bias assessment, and evidence of efficacy.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Cultural adaptations and individual tailoring, or subgroup analysis of outcomes of interest was not reported for the Asian American subgroups in these three large RCT studies. Following these study exclusions, seven studies were identified for review (Sun et al, 1996, Liao et al, 2002, Han et al, 2010, Qi et al, 2011, Dirige et al, 2013, Islam et al, 2013, Wang et al, 2013). Table 1 provides a descriptive summary of reviewed studies including: RTC design characteristics, sample characteristics, intervention characteristics, cultural appropriateness assessment, risk of bias assessment, and evidence of efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Three out of seven RCTs identified a theoretical framework to guide the intervention design. Two (Han et al, 2010, Qi et al., 2011) used Bandura's social cognitive learning and self-efficacy theory (Bandura, 1989), and one (Dirige et al, 2013) used the transtheoretical model (Prochaska and DiClemente, 1983). …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations